Long Term Effects of Tear Gases on Respiratory System: Analysis of 93 Cases - Peri Arbak; İlknur Başer; Özlem Ozdemir Kumbasar; Füsun Ülger; Zeki Kılıçaslan; Fatma Evyapan (The Scientific World Journal)
Aim. This study aimed to assess the long-term respiratory effects of tear gases among the subjects with history of frequent exposure. Materials and Methods. A questionnaire by NIOSH and pulmonary function tests was performed in 93 males exposed to the tear gases frequently and 55 nonexposed subjects. Results. The mean numbers of total exposure and last 2 years exposure were 8.4±6.4 times, 5.6±5.8 times, respectively. Tear gas exposed subjects were presented with a higher rate for cough and phlegm more than 3 months (24.7% versus 11.3%, P>0.05). Mean FEV1/FVC and % predicted MMFR in smoker exposed subjects are significantly lower than those in smoker controls (81.7% versus 84.1%, P=0.046 and 89.9% versus 109.6%, P=0.0004, resp.). % predicted MMFR in nonsmoker exposed subjects is significantly lower than that in nonsmoker controls (99.4% versus 113.1%, P=0.05). Odds ratios for chest tightness, exercise dyspnea, dyspnea on level ground, winter morning cough, phlegm, and daily phlegm were increased almost 2 to 2.5 folds among tear gas exposed subjects. Conclusion. The rates for respiratory complaints were high in the case of the exposure to the tear gases previously. Tears gas exposed subjects were found to be under the risk for chronic bronchitis.